Building Safe Didactic Dialogues for Action Model: Mobilizing Community with Micronesian Islanders - Connie K. Y. Nguyen-Truong; Jacqueline Leung; Kapiolani Micky; Jennifer I. Nevers (JMIR Publications, 2020)
Background: Despite mandates by the United States (U.S.) government to ensure the inclusion of women and minorities in federally funded research, communities of color continue to participate less frequently than non-Latinx Whites. There is limited research that examines maternal health outcomes and early childhood resources. Pacific Islanders (PI) have grown substantially in a county in the Pacific Northwest region of the U.S. (from 4,419 to 9,248, of which 52% are female). About 62.7% of PI women are not accessing prenatal care in the first trimester, and this is substantially higher than the national target of 22.1%. Researchers found that PI children are leaving school to take care of family obligations. The purpose of the educational innovative project, Building Safe Didactic Dialogues for Action model, was to respond to Micronesian Islanders (MI) parent leaders' need to feel safe and to build a close kinship to encourage dialogue about difficult topics regarding access and utilization of early education systems and prenatal/perinatal health for community-driven model for action planning and solutions. Approach: Popular education tenets were used in the project to be culturally sensitive to the human experience. The MI community health worker outreached to MI parent leaders in an urban area in the Pacific Northwest region of the U.S. Eight partners participated in this project: parent leaders from the MI community-at-large, community partners from the MI Community organization, and academic nurse researchers. Didactic dialogues lasted two hours per session for four. Topics included: collaborative agreements, MI parent leaders' identified needs and existing resources regarding preschool and immunization, parent-child relationship (stress and trauma, adverse childhood experiences), and MI experience regarding prenatal care access and postpartum depression. Group discussion on reflection was used to evaluate utility. Outcomes: Building Safe Didactic Dialogues for Action model was foundational via mobilizing community with MI, trust and rapport building, and engaging in a safe and courageous space for dialogues for action planning and solutions as community and academic partners as stakeholders. Conclusion: Many previously unspoken issues such as abuse, language, and cultural beliefs including barriers were openly shared among all partners. Dynamic thoughts towards identifying needs for change and then planning steps toward creating positive change created an atmosphere of empowerment for change.